Genetic variation in intronic region of GH1 gene and its potential as a marker for test day milk production traits in Holstein Friesian crossbred cattle - KOUR, ANEET; CHAKRAVARTY, A K; RAINA, VARINDER SINGH; YOUSUF, SALEEM; RATWAN, POONAM; KARUTHADURAI, T (The Indian Journal of Animal Sciences, 2019)
The study was conducted to find out the genetic variability in intron 3 region of GH1 gene and to estimate its effect on test day milk production traits in Karan Fries (Holstein Friesian crossbred) cattle. PCR-RFLP using MspI revealed two genotypes, namely BB and AB with frequencies as 0.18 and 0.82, and the frequency of B and A alleles as 0.59 and 0.41, respectively. Season of calving was found significant only for test day (TD) fat yield of TD3, TD6 and TD10. High association was found between test day milk traits and average lactation milk yield from TD3 onwards. TD1 and TD5 were found to be good for selection of animals as TD milk yield increased by 1.9352 kg and 0.9271 kg, TD fat yield by 101.2 g and 10.6 g and TD SNF yield by 188.8 g and 93.7 g respectively. The genetic variability in the targeted region could be further explored as a potential marker.